ANALISIS POHON FILOGENETIK GEN ITS1 Amanita muscaria DARI BERBAGAI NEGARA - Mutia Andini, Tri; Achyar, Afifatul (Jurnal Biogenerasi, 2025)
The purpose of this study is to determine the genetic diversity of the ITS1 gene from Amanita muscaria originating from various countries and create a phylogenetic tree based on ITS1 gene data to show the evolutionary relationship and distribution history of Amanita muscaria in various countries.The method used in this study is the Neighbor-Joining Method which is used to construct phylogenetic trees quickly and efficiently. Bootstrap tests (10,000 replicates) indicate the confidence level of the tree branches. Evolution was calculated using the Maximum Composite Likelihood method. The analysis involved 13 nucleotide sequences and was performed with MEGA11 software. The results of this study are The phylogenetic tree of Amanita muscaria shows two main clades with bootstrap values of 27 and 39, which reflect the level of confidence in the group of specimens. The first clade with a value of 27 includes specimens AB096048.1, AJ549964.1, AB080778.1, AB081295.1, and LN877747.1, while the second clade with a value of 39 includes AB015700.1, AB081294.1, AB080779.1, and AB080983.1. The branch with a bootstrap value of 63 shows greater genetic diversity. Specimens AB096048.1 and AJ549964.1 and AB080777.1 and AB096052.1 have very close evolutionary relationships.